Analisis Penerapan Sanitation Standard Operating Procedure (SSOP) dalam Produksi Permen Jelly Lidah Buaya - Yuniasih, Annisa Wirrdiana (Jurnal Ilmu-Ilmu Pertanian, 2025)
In order to maintain food safety, it is necessary to optimize the implementation of Sanitation Standard Operating Procedure (SSOP) in the food industry of a processed product. Guaranteed food security can meet quality and sustainable food security. The purpose of this study is to analyze and evaluate the application of SSOP in MSMEs "X", one of the MSMEs engaged in the cultivation and processing of aloe vera. The research was carried out in October-November 2022 with a qualitative descriptive research method. The results of the research analysis with the Miles and Huberman approach model found several shortcomings in the implementation of SSOP that have not been maximized by "X" MSMEs. There are several points that cannot be done properly to maintain food safety such as water safety, prevention or protection from adulteration, proper labeling or storage, and pest eradication. Employee hygiene and maintenance of tools that come into direct contact with materials are well understood and implemented. It is necessary to improve sanitation in production as much as possible according to existing standards, add some information on Production Operational Standards (SOPs) to the production room and improve the maintenance of equipment in accordance with food safety production standards.